Preparation of Adsorbent from Fly Ash for Methylene Blue Wastewater Treatment. Issue 1 (April 2019) - Liu, Dongji; Yang, Yuling; Zhao, Fengqing
Abstract: Fly ash contains SiO2 and Al2 O3, which account for more than 60% of the total. This is similar to the composition of zeolite which is frequently be used for adsorbent. Therefore, fly ash is used to prepare adsorbent for wastewater treatment by microwave-assisted hydrothermal method. The optimal reaction conditions were determined: alkali-ash ratio of 15:1, reaction temperature of 100°C and reaction time of 0.5h. The removal rate of methylene blue is up to 97.6%. The adsorbent was characterized by SEM and FT-IR. Large number of silicon (aluminum) oxygen tetrahedrons and the porous lattice structure contribute high adsorption performance of the adsorbent.